An Innovative Process to Select Augmented Reality (AR) Technology for Maintenance - Palmarini, Riccardo; Erkoyuncu, John Ahmet; Roy, Rajkumar (Elsevier, 2017)
Augmented Reality (AR) technology for maintenance aims to improve human performances by providing relevant information regarding both corrective and preventive maintenance. The development of an AR system involves the choice of a hardware, a development software and a visualisation method. These selections are challenging due to the wide choice of services and options available which result in fragmentation: different development processes and different user experiences. In order to ease the selection of an AR system for supporting maintenance operations, this paper proposes an innovative process. It guides the reader to identify the requirements and the constraints for any specific application through a number of questions developed in this study to help with the selection. This results in suggestions for the selection of the hardware, the development software and the visualisation method. The process is built based on a literature study, grey documents and experts interviews. Future works includes the validation of the selection process proposed in this project. It could be done by comparing the choices made using the proposed process with the choices made by experts for the same case study. Moreover, the decisional process could be extended to face the economical and ergonomics aspects related with the selection of an AR system. It could be done expanding the literature research including studies which investigate into the economical and ergonomics consequences of the application or AR for maintenance. Paper presented at The 5th International Conference on Through-life Engineering Services (TESConf 2016)
Keywords: Augmented Reality; Maintenance; Process